Fungal Diversity in Sediments From Deep-Sea Extreme Ecosystems: Insights Into Low- and High-Temperature Hydrothermal Vents, and an Oxygen Minimum Zone in the Southern Gulf of California, Mexico - Velez, Patricia; Salcedo, Diana L.; Espinosa-Asuar, Laura; Gasca-Pineda, Jaime; Hernandez-Monroy, Abril; Soto, Luis A. (Frontiers in Marine Science, 2022)
Deep-sea sediments are vast microbial habitats that cover almost two-thirds of the planet’s surface. Particularly, sediments in hydrothermal vents and oxygen minimum zones (OMZ) represent emblematic, and poorly understood extreme niches that pose strong selective pressures to life, representing untapped reservoirs of a unique microbial diversity. Nonetheless, the mycobiota in these systems remains relatively unknown. Here, we explored fungal diversity and community structure in deep-sea sediments collected from low- and high-temperature vent systems (Pescadero Basin, Pescadero Transform Fault, and Alarcón Rise) and an OMZ (Alfonso Basin) in the southern Gulf of California, by using high-throughput Illumina sequencing of the ITS1 region. We identified 102 fungal amplicon sequence variants (ASVs), principally affiliated to the Ascomycota and Basidiomycota. Our results also evidenced a high proportion of widely distributed, uncultured phylotypes (e.g., unknown clades closely related to the Basidiomycota such as Fungi sp. 18 and 19 formerly reported from deep-sea), evidencing the copious occurrence of novel fungal lineages with limited distribution to deep-sea sediments. Overall, the largest number of ASVs was recovered from high-temperature vent systems, corroborating these as diversity hotspots. In addition, clustering patterns across samples and the FUNGuild analysis revealed characteristic assemblages in each ecosystem, which could be linked to site-specific processes. This study provides baseline data paving the way for a better understanding of deep-sea fungal diversity, evidencing its potential importance in ecosystem functioning.